Benzothiadiazole-based non-fullerene acceptors. (September 2021) - Nie, Qingling; Tang, Ailing; Guo, Qiang; Zhou, Erjun
Abstract: The power conversion efficiencies (PCEs) of organic solar cells (OSCs) have been greatly improved with the rapid development of non-fullerene acceptors (NFAs) in recent five years. Among a great deal of electron-accepting units (A units), benzothiadiazole (BT) is the most important one and has been widely used to construct high-efficiency NFAs due to its unique electron-withdrawing properties, plane rigidity and structural adjustability. The optoelectronic properties of BT-based small molecules can be efficiently modulated with the location of BT unit in the molecular backbone. Typically, BT unit is used as an A1 unit to construct A2 -D-A1 -D-A2 and A2 -A1 -D-A1 -A2 type acceptors. Furthermore, DA'D -type fused BT-units can be utilized as a central segment to design A-DA'D-A type NFAs, which promote the rapid progress of OSCs from 2019. Judicious molecular engineering can finetune the energy levels of frontier molecular orbitals, absorption spectra, and the π-π staking properties of these materials. In turn, high-efficiency photovoltaic devices can be obtained by combining these BT-based NFAs with suitable p-type polymers. The highest PCE of OSC reached up to 18%, which could be mainly attributed to the emerge of the fused-BT-based molecule Y6. This review firstly made a precise classification of BT-based NFAs, and then summarized the relationship of chemical structures, molecular properties, and device performance. Finally, we looked forward to the challenges and design directions of this kind of molecules in the future. Graphical Abstract: Benzothiadiazole (BT) is the most important electron-accepting (A) unit and has been widely used to construct high-efficiency non-fullerene acceptors (NFAs). This review firstly made a precise classification of BT-based NFAs: single-BT, double-BT, multiple-BT and ring-fused BT. Then, we summarized the relationship of chemical structures, molecular properties, energy loss and photovoltaic performance. Finally, the challenges and design directions of this kind of molecules are prospected. ga1 Highlights: A comprehensive review on the development of BT-based non-fullerene acceptors (NFAs) was made. BT-based acceptor is an eximious material to obtain power conversion efficiency of more than 18%. This kind of acceptor has been systematically classified and the structure-property relationships were deeply summarized. An innovative prospect for the future development and the direction of industrialization of BT-based acceptors was made.